(untitled) (Communication & Society, 2007)
We will focus the study on three Spanish series, Médico de Familia, Los Serrano and Cuéntame cómo pasó. These series have some characteristics in common: they are targeted at family audiences; the family unit is the core of the story, their main plots are family related and they take place in the household. In addition, they are prime time series, which have reached high audience ratings, have a strong social incidence and have contributed to defining the image and the position of the broadcastings channels. Family target owns its specific characteristics that explain the way in which the contents are produced and commercialised. Therefore, it is very interesting for advertisers of products and services of collective and family goods, or whose consumption takes place at home. We will study the commercial aspects of the television drama, such as audience ratings, advertising income, merchandising and windowing rights and international sales.